Cancer type and gene signatures associated with breakthrough infections following COVID-19 mRNA vaccination - Youjia Zhong; Jiaqi Li; Ainsley Ryan Yan Bin Lee; Janice Yu Jin Tan; Carina Jing Xuan Tay; Clara WT Koh; Ethan Yong Tzi Seow; Wee Chee Yap; Shi Yin Wong; Chun En Yau; Chen Ee Low; Kelvin Bryan Tan; et al. (npj Vaccines)
Abstract We used epidemiological data from 21195 patients with cancer and 180407 matched controls, including in-depth analyses in 216 cancer patients, to discover clinical and molecular determinants that predispose cancer patients to breakthrough infections. Patients with B cell malignancies, with differential expression of CD24, CDK14 and PLEKHG1, were most susceptible to breakthrough infections, suggesting that these patients may require more booster immunisations to ameliorate cellular responses and immune protection against COVID-19.